Study on Influence of Diversified Parameters of Vehicle and Track on Wheel Hollow Wear - Yongjie Lu; Zongyu Gao; Jianxi Wang (Shock and Vibration)
Wheel hollow wear of high-speed train is one of the main damage types for the wheel. By optimizing the vehicle and track parameters and matching the wheel-rail profile, the hollow wear of wheel can be reduced. In order to study the sensitivity of vehicle and track parameters to the wheel hollow wear, the sensitivity of suspension parameters and the track parameters of the CRH2Ctype high-speed train wheel on the hollow wear of the wheel was studied by the parameter sensitivity analysis method. The concept of the cumulative wear power dissipation was put forward. The distribution characteristics of the wheel hollow wear under the different wheel/rail treads matching were forecasted. The results show that the damping of antihunting motion damper of the vehicle is the most sensitive to the maximum cumulative wear power dissipation of the wheel, followed by the longitudinal stiffness of tumbler journal box node, lateral stiffness of air-spring suspension, vertical damping of primary suspension, vertical stiffness of track, and vertical damping of track. According to the analysis from the combination of sensitive parameters, the cumulative wear power dissipation is unevenly distributed in the lateral direction of the wheel tread and has the obvious peak area, which is basically the same as the actual wear distribution location in the field. The matching of the LMA wheel tread and the CN60N rail tread is a good choice to slow down the hollow wear and reduce the wheel wear rate. And the wheel reprofiling should be timely carried out, otherwise the wear rate would increase and the hollow wear would become more serious.